Finding of Polydactyly and Syndactyly in an Eight-week Human Embryo. A Case Report - Maria Nelia Martínez Lima; María Aimée Vila Bormey; Yanely Surí Santos (Medisur)
The case of a human embryo at Carnegie stage 23 (eighth weeks), which belongs to the collection of embryos of the Faculty of Medicine in Villa Clara is presented. It was the result of the elective termination of pregnancy using misoprostol in a 41-year-old woman with 9.6 weeks of amenorrhea and a history of good health. The aim of this paper is to inform the diagnostic finding of polydactyly and syndactyly in a stage as early as the eighth week of development. Basic and clinical aspects of both malformations are described and the finding is shown through digital images. The importance of the morphological study of these products is emphasized, which would provide value judgments to genetic counselling in future pregnancies.